A programable biomimetic actuator with large and reversible deformation based on commercial poly (ethylene-co-vinyl acetate). (16th January 2023) - Li, Nan; Sun, Wen-Jin; Wang, Yue-Yi; Yan, Ding-Xiang; Li, Zhong-Ming
Abstract: Due to the reversible and remote actuation under applied voltage, shape-memory polymer (SMP) based on semi-crystalline polymer are explored for developing soft actuators, where the commercial material, poly (ethylene-co-vinyl acetate) (EVA), has great potential for the large-scale application to construct an actuator, due to its cost-effective and crystal-adjustable merits. However, the small deformation of SMP based on commercial poly (ethylene-co-vinyl acetate) (EVA) (usually less than 10%) is always a problem which limits their practical application. Herein, combining the pre-stretched and photo-crosslinked EVA, a biomimetic actuator with large reversible deformation (∼20%) is designed and fabricated by compounding with polyimide (PI) with screen-printed Ag conductive network. Using chemical crosslinking points as the new skeleton domain can allow the original crystal of the skeleton domain to involve in the reversible actuation to obtain large deformation. Meanwhile, due to the chemical crosslinking points formed by photo-crosslinking in EVA, the resultant composites can be actuated at temperatures above the melting point, which is critical to reducing the constraints of actuating conditions. In addition, the perfect conductivity prepared by the Ag conductive network endows this composite with a low voltage (≤25 V/m) actuating capacity. Based on the good programming capability of composites, various modes containing zero-set reversible actuation are designed. Particularly, a quadruped robot can stand up quickly under an applied voltage of 5 V and return to a zero-set state after voltage removal, which proves the application potential of the composite in flexible robotics. Graphical abstract: Image 1 Highlights: A low-voltage and large-deformation actuator with cost-effective and crystal-adjustable merits is proposed. The pre-stretched and photo-crosslinked EVA can fully release actuation, resulting in large reversible deformation (∼20%). A quadruped robot can achieve bionic movement within 5 V voltage, proving the potential of Ag/EVA/PI in flexible robotics.